Creative Thinking Level of Students in Posing Conditional Probability Problems - Sudi Prayitno; Dwi Novitasari; Tabita Wahyu Triutami; Ratna Yulis Tyaningsih (Universitas Syiah Kuala, 2023)
Mathematical creativity provides space for students to express their ideas. Hence, the mathematical activities should support their ability to pose and solve problems. However, students are not used to them and have difficulty in proposing and solving creative problems. The ideas proposed are in the form of problem-posing with free situational and semi-structural types and their solutions. This study aims to describe the level of creativity of students in problem-posing and problem-solving conditional probability problems. The research method used was qualitative, and participants were 35 second-year preservice mathematics teachers. The result indicates that, in posing a free situational type problem, students were generally at level 3 (creative) while, in posing a semi-structural problem, students were generally at level 0 (not creative). Although, the students in each type of problem-posing task were at the category of level 4 (very creative), level 3 (creative), level 2 (quite creative), level 1 (almost creative), and level 0 (not creative). This shows that there is a need for habituation for students to pose and solve problems, especially those that are related to semi-structural type problems.